Hemolysis research of implantable axial flow pump for two -step heart transplantation in children - O. Yu. Dmitrieva; A. S. Buchnev; A. A. Drobyshev; G. P. Itkin (Вестник трансплантологии и искусственных органов)
Introduction. One of the main indicators characterizing mechanical circulatory support devices (artificial valve, implantable pumps, etc.) is trauma of blood cells. Therefore, while developing new pumps, one of the key studies in vitro is to evaluate blood hemolysis. For an objective hemolysis analysis of pump it is required to create a standardized methodology of hemolysis studies. The object of the study in this paper is implantable axial pump DON for two-step heart transplantation in children.The aim of study is to develop a standardized methodology of hemolysis studies of blood pumps and to conduct research of pediatric axial pump DON.Materials and methods. To conduct hemolysis research we created a mock circulatory system consisting of a reservoir placed in water bath maintaining a constant working fluid (blood) temperature, hydrodynamic resistance, connecting tubes, ports for blood sampling and pressure and flow measurement systems, and research pump. Test method is to estimate levels of free hemoglobin pHb obtained by blood samples during pump working in operating mode (for pediatric pump: blood flow 2.5 l/min, pressure difference 80 mmHg). Using the data obtained the standardized indices of hemolysis NIH and MIH are calculated based on pHb values, hematocrit, total hemoglobin, blood flow and working pump time.Results. We developed and realized a standardized methodology of hemolysis research by which we evaluated hemolysis of pediatric axial pump. The results of hemolysis tests allowed us to optimize the design of DON. Obtained values of hemolysis of the latest version of pediatric pump DON-3 have shown that they do conform to the requirements of minimum blood injury and it allows us to proceed to the next step of pediatric pump research – animal experiments.Conclusion. Developed methods and evaluation tools of hemolysis allow us to provide objective information on one of the most important indicators of developing implantable pediatric axial pump and they could be recommended for hemolysis research of others pumps.